Neck forces and moments of human volunteers and post mortem human surrogates in low-speed frontal sled tests. (12th September 2016) - Beeman, Stephanie M.; Kemper, Andrew R.; Duma, Stefan M.
ABSTRACT: Objective: The objective of this study was to quantify the effects of active muscles (e.g. conscious bracing, resting tone, and reflex response) and acceleration severity on the neck forces and moments generated during low-speed frontal sled tests with adult male human volunteers and post mortem human surrogates (PMHSs). Methods: A total of 24 frontal sled tests were analyzed including male volunteers of approximately 50th percentile height and weight (n = 5) and PMHSs (n = 2). The tests were performed at two acceleration severities: low (∼2.5 g, Δv ≈ 5 kph) and medium (∼5.0 g, Δv ≈ 10 kph). Each volunteer was exposed to two impulses at each severity, one relaxed and one braced, while each PMHS was exposed to one impulse at each severity. Linear acceleration and angular velocity of the head were measured at a sampling rate of 20kHz, then filtered using SAE Channel Frequency Class 180 and 60, respectively, and transformed to the head center of gravity (CG). The location of the head CG, external auditory meatus, and occipital condyle (OC) were approximated using pretest photos and literature values. Neck forces (Fx and Fz) and sagittal plane moments (My) were calculated at the OC by applying the equations of dynamic equilibrium to the head. Results: Peak Fx, Fz, and My increased significantly with increasing acceleration severity (p < 0.1). Minimal differences were observed between the magnitudes of the peak forces and moments for each subject type. Qualitatively, differences in the timing of peak neck forces and moments and the overall shape of the time histories were evident. Maximum Fx, Fz, and My occurred earliest in the event for the braced volunteers and latest for the PMHSs. However, these differences were not supported statistically for the volunteers (p > 0.05). The timing of neck loading was visibly augmented by the increased stiffness of the volunteer necks as a result of muscle activation. Although differences were observed between the volunteer muscle conditions, the volunteer subsets were more similar to each other than the PMHSs. Conclusions: This study examined the effects of active muscles, in the form of conscious and reflexive muscle activity, on the biomechanical response of occupants in low-speed frontal sled tests. Although active bracing did not result in significantly different peak neck loads or moments, the timing of these peak values were affected by muscle condition. The findings of this study provide insight to the kinetics experienced during low-speed sled tests and are important to consider when refining and validating computational models and ATDs used to assess injury risk in automotive collisions.